Agroforestry in Ethiopia: Review of its Role in Enhancing Smallholder Agriculture, Environmental Sustainability, and Adoption Challenges - Tesema Habtamu Achenef; Shiferaw Hailie; Getachew Goremsu (Journal of Landscape Ecology, 2025)
Agroforestry, the integration of trees and shrubs into agricultural landscapes, has emerged as a promising strategy for enhancing smallholder agriculture in Ethiopia. The review’s overall objective was to examine the impacts of various agroforestry systems on the country’s agricultural productivity, food security, and environmental sustainability. However, synthesized fragmented evidence on adopting agroforestry systems among Ethiopian smallholders remains limited. The review used a combination of qualitative and quantitative methods to investigate agroforestry’s impact on smallholder agriculture, environmental sustainability, and adoption issues. A total of 89 publications were included in the systematic review, focusing on economic functions (n=40), environmental functions (n=35), and adoption challenges (n=20). Agroforestry is a land management strategy that integrates trees, crops, and livestock to generate food, protect the environment, and provide habitats for wildlife. The findings showed that agroforestry provides environmental functions such as soil fertility improvement, biodiversity conservation, soil and water conservation, and carbon sequestration. Moreover, agroforestry improves the economy of smallholder farmers by providing timber and non-timber products in Ethiopia. The review result indicated that key challenges, including socio-economic barriers, limited resource access, and inadequate extension services, hinder the widespread adoption of agroforestry. The findings emphasize the need for targeted policies and support mechanisms to overcome these challenges and maximize the potential of agroforestry in contributing to sustainable agricultural development in Ethiopia. The review concludes by suggesting pathways to enhance adopting agroforestry systems in Ethiopia, emphasizing the need for integrated approaches combining scientific innovations with local practices to support sustainable agricultural development.